Manajemen Lingkungan Masyarakat Melalui Pendekatan Culture and Behavior di Pesisir Timur Sumatera Utara - A. Hadian Pratama Hamzah; Nurhasanah Nurhasanah (Universitas Batanghari, 2023)
Human activities on the environment are inseparable from the by-products in the form of waste, for example paper, plastic, metal, glass or glass are by-products of human activities on the environment. Solid waste control does not only cover the environment in urban areas but rural areas on the coast is a global issue that has not been resolved. One way that can be taken in dealing with solid waste in the environment is through a cultural approach and local community knowledge. This study aims to identify the local wisdom of the community called